Energy band structure, elastic and optical constants of the filled skutterudite CeRu4As12. (May 2016) - Shankar, A.; Rai, D.P.; Sandeep,; Joshi, H.; Khenata, R.; Ghimire, M.P.; Thapa, R.K.; Mandal, P.K.
Abstract: The energy band structure and the optical response of the filled skutterudite CeRu4 As12 have been studied using the full-potential linearized augmented plane wave (FP-LAPW) method within the local density approximation (LDA). The analysis of the region close to the Fermi energy level suggests the narrow band gap (0.18 eV) semiconducting nature of the material. The new approach of the exchange-correlation functional called the modified Becke Johnson potential used in the treatment of the material gives an enhanced band gap value of ~0.2 eV. The elastic parameters are also estimated at the ambient condition, which indicates the brittle nature of the studied material. The study of the optical spectra suggests the metallic behavior of the material in the far infrared region, which indicates that it acts as an opaque material with superluminal behavior in the ultraviolet frequency.